TD 3. Sustainable Irrigation Water Management Using ICT Tools for Monitoring and Reporting of Water Demand on Rice Irrigation Systems (The Philippine Journal of Crop Science, 2018)
In irrigated areas, the alternate wetting and drying (AWD) technique saves water up to 30% without yield penalty and has many benefits, including reductions of methane emissions. AWD is a mature technology where the field is allowed to dry except at (1) seedling recovery phase until 2 - 4 weeks after transplanting until weeds are controlled and (2) during flowering stage. Irrigation is applied when the water level in the field is 15 cm below the soil surface. Although AWD has been tested and validated in many countries, its adoption has been relatively slow because of the many challenges faced by farmers. The major challenges are (a) water governance–water is managed by an irrigators'/farmers' association instead of by individual farmers (b) decision platform: the technology at this stage is field specific and can't be extrapolated to the turnout catchment area; the approach lacks the interface for converting data into information for other stakeholders in the irrigation system hierarchy; (c) knowledge-intensive–this technique requires good understanding and measurement of water depth; (d) labor-intensive–the frequent monitoring flooding and drying of paddy fields increase costs; and (e) time-intensive–the new technique requires more management oversight and puts higher demands on farmers' time. To overcome these challenges IRRI and DA-Philice have developed an ICT tool called AutoMonPH for catalyzing the adoption of water saving technologies by improving access to the information, effective coordination among different decision makers, and transparency in water governance. The decision tool was demonstrated in Regions 2, 3, and 6 to evaluate the performance in terms of accuracy and sending of data. Results showed very high correlation between AutoMonPH readings and manual readings (R2-0.99). An interface is being developed to analyze the data at different scales and send information to different stakeholders depending on their role in water governance.